(z+yi)2=-12-10i

Take the square root of each side of the equation to set up the solution for z

(z+yi)2⋅12=±-12-10i

Remove the perfect root factor z+yi under the radical to solve for z.

z+yi=±-12-10i

First, use the positive value of the ± to find the first solution.

z+yi=-12-10i

Subtract yi from both sides of the equation.

z=-12-10i-yi

Next, use the negative value of the ± to find the second solution.

z+yi=–12-10i

Subtract yi from both sides of the equation.

z=–12-10i-yi

The complete solution is the result of both the positive and negative portions of the solution.

z=-12-10i-yi

z=–12-10i-yi

z=-12-10i-yi

z=–12-10i-yi

Solve for z (z+yi)^2=-12-10i